Dependência, questão agrária e globalização: interpretações econômico-políticas e jurídicas da estrangeirização da terra no Brasil - Bueno, Igor Mendes (2019)
This study aims at comprehending how the actual land foreignization process in Brazil - legally consolidated along with the flexibilization of normative landmarks on the acquisition of land by physical and legal foreign people - is related with the new phase of dependence and the agrarian question in Latin America and, more specifically, in the country, besides the scenario of neoliberal globalization. Thus, we demonstrate how the process of flexibilization of legal normatives related to land sale for foreigners in Brazil, which occurs since the 1990s, in the context of the neoliberalism arrival in the country, it is a process that relates integrally to a whole new framework that combines the new phase of Latin American dependence, the structural crisis of capitalism, and the globalization in the neoliberal standards. This phenomenon is presented therefore as much a consequence of these processes interconnected with the global crisis of capitalism as it is also a fundamental part of the constitution of new chains of the structural condition of dependence, which means, in the last degree, a movement from the financial capital globalized by the constitution of a global land market for the direct capture of land income. So on, starting from the theoretical-methodological matrix of dialectical materialism, we articulate theoretical references of the critical theories of development, especially of the Marxist Theory of Dependence (mainly Theotonio dos Santos, Ruy Mauro Marini e Mathias Seibel Luce), alongside with the studies on Latin American and Brazilian agrarian question (above all Caio Prado Jr., José de Souza Martins e Roberta Traspadini), about the capitalism crisis and globalization in the neoliberal molds (Carlos Eduardo Martins e David Harvey), as also numerous most recent studies on the phenomenon called land grabbing or “corrida mundial por terras”.